2009
DOI: 10.1177/0883073809336295
|View full text |Cite
|
Sign up to set email alerts
|

Branched Chain Amino Acids as Adjunctive Therapy to Ketogenic Diet in Epilepsy: Pilot Study and Hypothesis

Abstract: A pilot prospective follow-up study of the role of the branched chain amino acids as additional therapy to the ketogenic diet was carried out in 17 children, aged between 2 and 7 years, with refractory epilepsy. All of these patients were on the ketogenic diet; none of them was seizure free, while only 13 had more or less benefited from the diet. The addition of branched chain amino acids induced a 100% seizure reduction in 3 patients, while a 50% to 90% reduction was noticed in 5. Moreover, in all of the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 23 publications
1
23
0
9
Order By: Relevance
“…In recent years, however, considerable research has focused on the possibility that less onerous increases of branched-chain amino acids and ketoacids might prove beneficial in preventing brain injury, possibly by subtly modulating intra-cerebral levels of glutamate and/or glutamine. To this end, investigators have scrutinized the therapeutic potential of dietary branched-chain amino acid supplementation in diverse pathologic conditions, among them hepatic encephalopathy (Dam et al, 2013; Bak et al, 2013), fatigue (Newsholme and Blomstrand, 2006; Choi et al, 2013; Gluud et al, 2013), traumatic brain injury (Cole et al, 2010); appetite and energy sensing (Schwartz, 2013), obesity (Drgonova, 2013) and epilepsy (Evangeliou et al, 2009). It is probable that future investigation will broaden this repertoire still more.…”
Section: Branched-chain Amino Acids As a Source Of Brain Glutamate Nmentioning
confidence: 99%
“…In recent years, however, considerable research has focused on the possibility that less onerous increases of branched-chain amino acids and ketoacids might prove beneficial in preventing brain injury, possibly by subtly modulating intra-cerebral levels of glutamate and/or glutamine. To this end, investigators have scrutinized the therapeutic potential of dietary branched-chain amino acid supplementation in diverse pathologic conditions, among them hepatic encephalopathy (Dam et al, 2013; Bak et al, 2013), fatigue (Newsholme and Blomstrand, 2006; Choi et al, 2013; Gluud et al, 2013), traumatic brain injury (Cole et al, 2010); appetite and energy sensing (Schwartz, 2013), obesity (Drgonova, 2013) and epilepsy (Evangeliou et al, 2009). It is probable that future investigation will broaden this repertoire still more.…”
Section: Branched-chain Amino Acids As a Source Of Brain Glutamate Nmentioning
confidence: 99%
“…(2015) 4 , it is indeed likely that the nutritional strategies employed in our CD concur to downregulate the LDH metabolic pathway, a component of the astrocyte-neurone lactate shuttle. It also remains probable that other mechanisms act in parallel to dampen neuronal excitation, such as for instance reduced glutamate level in the brain that could result from a high BCAA/AAA ratio 19, 20 , or neuronal hyperpolarization induced by polyunsaturated fatty acids though modulation of voltage gated ion channels 39 , or the increase in adenosine receptors activation under medium-chain triglycerides treatment, which reduces probability of neurotransmitter release 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Also supporting this approach, glycolytic inhibition with 2-deoxyglucose administration has proved effective in reducing seizure occurrence in epilepsy models 17, 18 . Finally, interesting data suggest that the proportion of branched-chained (BCAA) vs aromatic amino acids (AAA) in the blood can influence excitability of central neuronal networks 19, 20 . The BCAAs leucine, isoleucine and valine would indeed favour ketosis and GABA synthesis while reducing glutamate levels 19, 21 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With a therapy as carefully calculated as the KD, it is natural for parents and dietitians to want to attempt many dietary modifications, especially when seizures recur after initial improvement. A single study recently suggested that adding branched-chain amino acids to the KD might improve efficacy [26]. However, the cohort chosen had already improved to some degree with the KD.…”
Section: Top 10 Dietary Therapy Research Issuesmentioning
confidence: 99%